Heat transfer performance study of microchannel heat sink with composite secondary channels. (April 2023) - Wen, Haiping; Liang, Zhixuan; Luo, Qingyi; Wu, Chili; Wang, Changhong
Abstract: To enhance the performance of microchannel heat sinks, secondary channels or ribs are oftenused separately. However, the synergistic enhancement of heat dissipation by secondary channels and individually composite with different types of ribs and the factors influencing them are not yet clear. In this study, the numerical simulation software ANSYS Fluent is used for simulation and obtaining the optimal microchannel heat sink structure from diamond, rectangular, back triangular, front triangular and elliptical ribs with secondary channel composite. Firstly, the results show that overall performance of microchannel heat sink with front triangular ribs with secondary channel composite is better than other designs. Secondly, the optimized microchannel heat sink with front triangular ribs and secondary channels outperforms the conventional microchannel heat sink by up to 34% in terms of overall performance when Reynolds number is 200, relative rib width/rib length is 0.633/0.400 and relative secondary channel width is 0.600. Finally, by sensitivity analysis, it is found the effect of relative rib width on heat dissipation is about 60%, the effect of flow rate on pressure drop is about 40%, and the effect of overall performance on relative rib width and relative secondary channel width are about 26% and 25%, respectively. Highlights: The heat transfer mechanism of composite microchannels is studied by Heat Transfer. The optimal rib shape is obtained by comprehensive performance. The relevant parameters are optimized to obtain the best composite microchannel. Maximum factors affecting heat transfer, pressure and overall factor are obtained.